Price efficiency on Islamic banks vs. conventional banks in Bahrain, UAE, Kuwait, Oman, Qatar and Saudi Arabia: impact of country governance - Kamarudin, Fakarudin; Sufian, Fadzlan; Md. Nassir, Annuar; Mohamad Anwar, Nazratul Aina; Ramli, Nur Ainna; Tan, Khar Mang; Hussain, Hafezali Iqbal (Inderscience Enterprises, 2018)
This research investigate the impact of six dimensions of country governance to the price efficiency of Islamic and conventional banks. The empirical analysis is focused on the Islamic and conventional banks operating in the Bahrain, UAE, Kuwait, Oman, Qatar and Saudi Arabia countries. The data envelopment analysis (DEA) method applied to compute the revenue efficiency of Islamic and conventional banks. Then used the Multivariate Panel Regression Analysis with the Ordinary Least Square as an estimation method to investigate the potential determinants and the effect of country governance on the revenue efficiency. The empirical findings indicate that greater voice and accountability, political stability, regulatory quality, rule of law and control of corruption enhance the revenue efficiency of both Islamic and conventional banks. The dimension of government effectiveness exerts positive sign relationship with the banks revenue efficiency only on conventional banks.